Women's well-being during Covid-19 pandemic - Hasbullah, Muslihah; Juhari, Rumaya; Madon, Zainal; Mansor, Mariani; Kahar, Rojanah; Daud, Mohd Najmi; Ismail, Nellie; Dahamat Azam, Mohamad Naqiuddin (Human Resource Management Academic Research Society, 2021)
The official declaration of the Movement Control Order (MCO) since March 2020 in Malaysia signifies a major step taken by the government to contain the COVID-19 pandemic effectively. This cordon sanitaire has devastating effects on all sectors and ordinary citizens, especially for women (United Nations, 2020). The socio-economic implications of MCO on women requires attention and proper handling. Using data from 841 women, the participants of Family and Community Empowerment Program (FACE), this study explores the extent of changes in the lives of women amid COVID-19. This study describes the socio-economic status (SES) and the well-being of respondents during the implementation of MCO. The Personal Wellbeing Index-Adult (PWI) is used to measure the well-being of these women. Results of the study highlight the immediate effect of MCO on the employment status and income of the respondents. Respondents reported lower mean scores on four domains, i.e. future security (M=7.21, SD=1.79); the standard of living (M=7.31, SD=1.88); achievement in life (M=7.36, SD=1.82); and community-connectedness (M=7.39, SD=1.85). The differences in PWI based on the SES of the respondents are also discussed. This study emphasises on the response and recovery efforts that are tailored to support women during this infectious-disease outbreak.